1994
DOI: 10.1099/13500872-140-12-3379
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of polyketide synthase genes for jadomycin B biosynthesis in Streptomyces venezuelae ISP5230

Abstract: Hybridizing fragments in the genomic DNA of Streptomyces venezuelae lSP5230, which produces the jadomycin group of angucycline antibiotics, were detected by probing with act/ DNA from Streptomyces coelicolor A3(2). The hybridizing regions were isolated from a 16.5 kb insert of S. venezuelae DNA recovered from a genomic library cloned in a A replacement vector. Subcloning and sequencing of a 4 8 kb segment of the insert, containing regions hybridizing to act/// as well as act/, identified five open reading fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 32 publications
1
78
0
Order By: Relevance
“…The 2.4 kb fragment isolated from SacI-digested i LH7 DNA (Han et al, 1994) was subcloned in both orientations in the Sac1 site of pBluescript I1 SK( + ). The recombinant phagemids (p JV60/61) were digested with exonuclease I11 and ligated to generate overlapping deletion clones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2.4 kb fragment isolated from SacI-digested i LH7 DNA (Han et al, 1994) was subcloned in both orientations in the Sac1 site of pBluescript I1 SK( + ). The recombinant phagemids (p JV60/61) were digested with exonuclease I11 and ligated to generate overlapping deletion clones.…”
Section: Methodsmentioning
confidence: 99%
“…Cloning and sequence analysis of a fragment of S. venepuelae ISP5230 genomic DNA that hybridizes with act genes from Streptomyes coelicolor A3(2) established the presence of a polyketide synthase (PKS) gene cluster in S. venextrelae. Selective loss of jadomycin B production when a plasmid containing part of the cloned sequence integrated into the chromosome indicated that the PKS genes are associated with jadomycin biosynthesis (Han et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Three and nine KSa sequences from G. glabra and G. inflate strains, respectively, formed a cluster with KSa sequences related to the biosynthesis of angucycline antibiotics (Han et al, 1994) (Fig. 3).…”
Section: Phylogenetic Diversity Of Type II Pks Gene Cluster Ksa Genesmentioning
confidence: 99%
“…The atypical angucycline antibiotic jadomycin B (1) and its aglycone jadomycin A (2) are produced in cultures of Streptomyces venezuelae ISP5230 grown under stress conditions in a medium containing isoleucine (6,7). The angucycline origin of jadomycins was verified by accumulation of a well known antibiotic rabelomycin (3) in the jadF disruption mutant VS655 (7) and by production of UWM6 (4) in Streptomyces lividans transformed with the jad PKS gene cluster (i.e.…”
mentioning
confidence: 99%